HEAVY METALS IN A DOMINANT SEAWEED SPECIES FROM THE ISLANDS OF INDIAN SUNDARBANS: Life Sciences-Environmental Science - PROSENJIT PRAMANICK; SUFIA ZAMAN; TANMOY RUDRA; ARNESHA GUHA; ABHIJIT MITRA (International Journal of Life Science and Pharma Research, 2022)
We analyzed the concentrations of heavy metals (Fe, Mn, Zn, Cu, Co, Pb and Ni) in a dominant seaweed species (Enteromorpha intestinalis) collected from the islands of Indian Sundarbans deltaic complex during 2013-14 using AAS. The order of accumulation of heavy metals is Fe > Mn > Zn > Cu > Co > Pb > Ni. The bioaccumulation of heavy metals in E. intestinalis exhibited pronounced spatial variation, which may be attributed to type and degree of anthropogenic stress operating in and around the sampling stations.